Development, characterization and in vitro cytotoxicity of kaempferol-loaded nanostructured lipid carriers in glioblastoma multiforme cells - Nicoleti, Luisa Ribeiro [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Duarte, Jonatas Lobato [UNESP]; Luiz, Marcela Tavares [UNESP]; Sábio, Rafael Miguel [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2023)
Glioblastoma multiforme is the most common and most aggressive human brain cancer. GBM treatment is still a challenge because many drugs are not able to cross the blood-brain barrier, in addition to the increasing resistance to currently available chemotherapy. New therapeutic alternatives are emerging, and, in this context, we highlight kaempferol, a flavonoid with remarkable anti-tumor activity but with limited bioavailability due to its strong lipophilic property. A promising tool to improve the biopharmaceutical properties of molecules such as kaempferol is the use of drug-delivery nanosystems, such as nanostructured lipid carriers (NLC), which can facilitate the dispersion and delivery of highly lipophilic molecules. The present work aimed at the development and characterization of kaempferol-loaded NLC (K-NLC) and the evaluation of its biological properties using in vitro models. The K-NLC showed an average size of 120 nm, zeta potential of − 21 mV, and polydispersity index of 0.099. The K-NLC presented high kaempferol encapsulation efficiency (93%), a drug loading of 3.58%, and a sustained kaempferol release profile for up to 48 h. In addition to presenting a 7-fold increase in kaempferol cytotoxicity, its encapsulation in NLC promoted a cellular uptake of 75%, which corroborates with increased cytotoxicity in U-87MG cells, as observed. Together, these data reinforce the promising antineoplastic properties of kaempferol in addition to the key role of NLC as a platform for the efficient delivery of lipophilic drugs to neoplastic cells, which improved their uptake and therapeutic efficacy in glioblastoma multiforme cells.
Keywords: Brain cancer; Drug delivery; Flavonoids; Lipid nanoparticles